(untitled) (European Journal of Pure and Applied Mathematics, 2023)
In this papers, we investigate the Hankel determinant and Toeplitz determinant for the class Bazileviˇc Function B1(α, δ) related to the Bernoulli Lemniscate function on the unit disk D = z : |z| < 1 and obtain the upper bounds of the determinant H2(1), H2(2), T2(1), and investigate H2(1) using coefficients invers function. We used lemma from Charateodory-Toeplitz and Libera about sharp inequalities for functions with positive real part.